Kinetika Reaksi Hidrogenasi Ester Lemak Menjadi Alkohol Lemak Dengan Katalis Tembaga- Mangan - Gunawan, Melia Laniwati; Makertihartha, IGBN; Subagjo, Subagjo (Indonesian Journal of Chemical Research, 2020)
Fatty alcohol (FAOH) can be produced by hydrogenating of fatty acid methyl ester (FAME) using the copper-based catalyst. Copper-Chrom (Cu-Cr) is the best catalyst for high-pressure reaction condition, which is copper (Cu) as the main active component and chrom (Cr) as a promoter. Since Cr is feared to be toxic, one of the best replacement candidates is manganese (Mn). The research aims is to find the kinetic equation of hydrogenation FAME to FAOH using a Cu-Mn commercial catalyst. FAME with methyl laurate and methyl myristate as the main compounds is used as feedstock. The main products are lauryl alcohol and myristyl alcohol. The reaction was carried out in an isothermal continuous fixed bed reactor under conditions of temperature 220 – 240 oC, pressure 50 bar, and liquid hourly space velocity (LHSV) 5-12.5 hr-1. The kinetic equation is determined using the power law model. The FAME hydrogenation on copper - manganese catalyst is the half order reaction. The activation energy value is 86.32 kJ/mol and the Arrhenius constant value is 5.87x106 M0.5/s.